Liturgy of the Hours and the Lectio Continua of the Psalter - Dieter Böhler (Religions)
In the last 40 years, the exegesis of the Psalms has made it increasingly clear that the Psalms should be read as a coherent book, since the individual Psalms are linked together by iuxtapositio and concatenatio. They are not just isolated poems but tell a story, the story of David, God’s anointed king who is persecuted and suffers, but ultimately is triumphant—a Christological story. This article examines how the principle of lectio continua of the Psalter is taken into account in the breviaries of Pius V, Pius X and Paul VI, and it shows what problems arise when it is disregarded.